0830 A population-based study of paediatric onset multiple sclerosis. Issue 3 (9th February 2012) - Liang, K; Baker, K E; Cossburn, M D; Ingram, G; Hirst, C L; Pickersgill, T P; Robertson, N P
Abstract : Background: There remains scarce population-based data on paediatric onset disease (POMS), which are commonly limited by low incidence and diagnostic difficulties. However, POMS provides important insights into the early impact of genetic and environmental factors. Methods: 105 POMS and 1811 adult onset (AOMS) patients were studied over a mean follow-up of 15.5 yrs. Features of early disease and times to disability milestones were examined. Genotyping for HLA DRB*1501 and 14 non-HLA disease associated SNPs was performed and total risk allele data compared. Results: No differences in disease ignition characteristics were observed between POMS and AOMS (p=0.76). The POMS cohort took longer to reach disability milestones compared to AOMS (EDSS 4 p<0.01; EDSS 6 p<0.01; EDSS 8 p=0.02), but milestones were attained younger (EDSS 4 37.4 vs 46.8 yr, p<0.01; EDSS 6 44.1 vs 52.3 yr, p<0.01; EDSS 8 64.9 vs 68.9 yr, p<0.01). There was no difference in familial disease recurrence rates, HLA-DRB1*1501 allele carriage (p=0.26) or cumulative number of MS susceptibility risk alleles (p=0.69). Conclusion: Clinical features and genotyping profiles for of POMS are similar to those observed in AOMS. However, although generally considered to have a benign course POMS patient acquire fixed disability at a younger age than AOMS and have a worse age-related prognosis.